The Effectiveness Of Criminal Sanctions As An Instrument Of Prevention And Enforcement In The Legal Framework Of Money Laundering Crimes - Hanif Fonda; Evita Isretno Israhadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Money laundering is a serious crime that has a significant impact on economic and social stability, as well as the integrity of the financial system. This crime is often associated with serious crimes such as corruption, narcotics, and terrorism. Money laundering poses a major threat to national security, conceals the origin of illicit funds, and undermines a healthy economic system. To combat this crime, Indonesia has imposed criminal sanctions based on Law Number 8 of 2010, which aims to provide a deterrent effect on perpetrators and prevent similar crimes from occurring in the future. However, the effectiveness of these criminal sanctions remains a critical challenge, given the various difficulties in their enforcement, such as the complexity of tracking the flow of funds, limited law enforcement resources, and the increasingly sophisticated modus operandi of perpetrators who often work together with international networks. This study seeks to examine the effectiveness of criminal sanctions in combating money laundering and identify obstacles in their implementation. The research method used is juridical-normative research with a legal regulatory framework. Primary data was obtained through literature review and examination of legal documents, while secondary data came from relevant literature, reports, and academic studies. The urgency of this research stems from the importance of evaluating and strengthening the application of criminal sanctions to protect the national financial system from the risk of money laundering. Without concrete steps to increase the effectiveness of sanctions, money laundering crimes will continue to proliferate and pose a threat to the national economy, weaken the legal system, and erode public trust in efforts to combat economic crime.